Analisis Penerapan Teknologi Sensor Berbasis Iot dalam Pemantauan Ketinggian Air Sungai - W. Indra Wallasia Putra; Toha Saleh (Syntax Corporation Indonesia, 2024)
This research aims to compare conventional methods and Internet of Things (IoT) based sensors in measuring river water level. Conventional methods involve the use of manual measurement equipment and fixed measurement stations, while IoT-based sensors use sensor technology that is connected directly to an online monitoring system. This research was carried out by conducting a literature study and obtaining data on the water level of the Ciliwung River which was measured using the peilschaal method by BBWS Ciliwung Cisadane and the IoT-based electromagnetic sensor method by PANTIR (Pemantau Tinggi Air). Comparison of the two measurement methods is carried out from the aspect of accuracy of measurement data and performance based on the time required to obtain the data. The results obtained are in the form of a qualitative analysis which shows the advantages and disadvantages of each method.